Integrated hedonic-utilitarian valuation of the built environment by neutrosophic INVAR method. (February 2021) - Zavadskas, Edmundas Kazimieras; Kaklauskas, Arturas; Bausys, Romualdas; Naumcik, Andrej; Ubarte, Ieva
Graphical abstract: Highlights: Neuro decision matrices were applied in the multiple criteria analysis of the alternatives. Neutrosophic INVAR method was applied to analyze affective attitudes, emotional and physiological states, etc. in housing. Neutrosophic INVAR method calculate the integrated hedonic-utilitarian value of the housing under analysis. Neutrosophic INVAR method provides digital guidelines for improving the housing. Neutrosophic INVAR method computes indicator values allowing the housing to upgrading to a desired score. Abstract: Hedonic valuation models enable us to make relevant decisions concerning the equipage of the built environment amenities and to establish more correct price zoning and land use management. These studies examining the utilitarian and hedonic aspects of property often face issues: how can we measure and assess multisensory experiences of property buyers (their affective attitudes, emotional states and physiological parameters) in an integrated manner and make a decision? This fact was a vital goal of the integrated Neutrosophic Degree of Project Utility and Investment Value Assessments along with Recommendation Provisions (INVAR) method. About 200 million multisensory data points have been collected so far and, as a result of their correlation analysis, several tens of thousands of average and robust correlations were determined. The new Neutrosophic INVAR method offers a bigger, more detailed picture of the hedonic-utilitarian value of the property. Another benefit of the Neutrosophic INVAR method is its ability to assist in assessing any project, determining its integrated hedonic-utilitarian value and offering tips on ways to make the project better. The Neutrosophic INVAR method can also optimise any criterion of your choice to make a specific project as competitive in the market and can determine the value that would propel the project to the top among the projects discussed. The analysis performed in this research is the basis for asserting that a sustainable development policy for housing and a surrounding environment is only possible by analysing the two-way process of interactions between a built environment and its neighbourhood residents in an integrated manner.